Do Consumers Acquire Information Optimally? Experimental Evidence from Energy Efficiency - Andrea La Nauze; Erica Myers (Center for Economic Studies and ifo Institute (CESifo), 2023)
We use an experiment to test whether consumers optimally acquire information on energy costs in appliance markets where, like many contexts, consumers are poorly informed and make mistakes despite freely available information. To test for optimal information acquisition we compare the average utility gain from improved decision making due to information with willingness to pay for information. We find that consumers acquire information suboptimally. We then compare two behavioral policies: a conventional subsidy for energy-efficient products and a non-traditional subsidy paying consumers to acquire information on energy costs. The welfare effects of each policy depend on the benefits of improved decisions versus the losses of mental effort (from the information subsidy) or distorted choices (from the product subsidy). In our context, information subsidies dominate product subsidies. In a variety of settings where decisions are made and information is delivered online, paying for attention could more effectively target welfare improvements.
Keywords: D91; D12; D83; Q41; 330; endogenous information acquisition; behavioral bias; information interventions; energy efficiency